Assessment of genetic diversity in natural European hophornbeam (Ostrya carpinifolia Scop.) populations in Turkey - Semsettin Kulac; Ertugrul Filiz; Emrah Cicek; Zerrin Degermenci; Recep Vatansever (Biotechnology & Biotechnological Equipment, 2016)
Genetic diversity is a crucial component for plant survivability and fitness in terms of adaptation, genetic stability and variability. In this study, a total of 160 genotypes were investigated using 12 random amplified polymorphic DNA (RAPD) primers to understand the genetic structure and diversity of nine naturally distributed Ostrya carpinifolia populations in Turkey. Twelve RAPD primers yielded 111 clearly identifiable DNA bands, of which 71 bands were found to be polymorphic (64%). Observed number of alleles (Na), effective number of alleles (Ne) and Nei's gene diversity (h) were found as 2, 1.53 and 0.32, respectively. Total genetic variation (HT), within-population genetic variation (HS) and Nei's genetic differentiation coefficient (GST) were found as 0.32, 0.09 and 0.70, respectively. Genetic diversity analysis (AMOVA) revealed highly significant (P < 0.001) genetic variations among and within populations. 69.94% of total variation was observed among populations while 26.69% was within populations. Gene flow value was calculated as 0.21 (Nm < 0.5), which could homogenize the genetic structure of a population. Two geographically isolated populations demonstrated high gene diversity and polymorphic loci ratio, indicating a relationship between geographic distribution of populations and eco-geographic factors. The findings of this study will pave the way for understanding the genetic diversity between inter- and intra-populations of O. carpinifolia species, as well as they would provide valuable information for management, conservation and utilization of in situ and ex situ Ostrya germplasms.